(untitled) (Revista Española de Fisiología, 1965)
A description is made of the apparition of a Crabtree effect on yeast homoge nates obtained through pulverizing in a mortar with alumina. The incidence of this effect has some connection with the relative proportions in which we find glucose and ATP, as it appears tvhen the concentration of glucose is greater than that of ATP. This effect disappears by the addition of either ADP or ethanol, which leads us to suspect the intervention of control mechanisms more complex than the simple competition for ADP by part of the glycolitial and respiratory systems.